2018
DOI: 10.1093/trstmh/try100
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in children with central nervous system disorders in Mansoura, Egypt: a case–control study

Abstract: The association between Toxoplasma infection and neurological disorders in children should be kept in mind by paediatricians and assessment of T. gondii antibodies in early childhood is needed for timely management of afflicted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…This difference mirrors a plausible association between toxoplasmosis and neurological disorders. The results corroborated those of our preliminary study on 30 children suffering from central nervous system manifestations without obvious chromosomal anomalies, 30 children with Down syndrome and 30 healthy children [18] . This association was also previously reported by Zaki et al [19] who detected a high seropositivity of anti-Toxoplasma IgG (35.8% vs 14.8%) in neuropsychiatric patients at KSA than controls, but no significant association was reported between anti-Toxoplasma IgM seropositivity and neuropsychiatric disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This difference mirrors a plausible association between toxoplasmosis and neurological disorders. The results corroborated those of our preliminary study on 30 children suffering from central nervous system manifestations without obvious chromosomal anomalies, 30 children with Down syndrome and 30 healthy children [18] . This association was also previously reported by Zaki et al [19] who detected a high seropositivity of anti-Toxoplasma IgG (35.8% vs 14.8%) in neuropsychiatric patients at KSA than controls, but no significant association was reported between anti-Toxoplasma IgM seropositivity and neuropsychiatric disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Our results show rates of 8.3% and 17.4% seropositivity for anti-Toxoplasma IgM and IgG respectively among children group manifested by Down syndrome with a statistically significant association between Down syndrome and toxoplasmosis in comparison to control group. To our best knowledge, there is no previous data on the relation between children with Down syndrome and T. gondii seropositivity except our previous study [18] that demonstrated seropositivity rates of 3.33% and 13.33%, respectively. However, the study of Shehata et al [20] reported higher rates of anti-T. gondii IgM and IgG antibodies in patients with Down syndrome (10.3% and 34.5%, respectively).…”
Section: Reviewingmentioning
confidence: 63%
“…IgG seroprevalence rate among children with DS in the present study is lower than that (13.3%) recently reported among Egyptian children with DS in Mansoura governorate [12]. It is also lower than that reported among apparently healthy children (16.0%; 40/250) and children with visual and/or hearing disabilities (32.5%; 39/120) in Taiz city, southwest of Yemen [21].…”
Section: Discussioncontrasting
confidence: 80%
“…opene pi. com) based on the following parameters: DS population of 250 registered children, a 95% confidence level, an expected seroprevalence of 13.3% according to the single available estimate of T. gondii seroprevalence among Egyptian children with DS [12] and an accepted marginal error of 5.0%. However, 107 children with DS were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Hamed et al (2018) showed a significantly high prevalence of anti-T. gondii IgG in mentally retarded children (42%) attending Cairo University hospital, when compared to the controls (17.5%). However, El-Beshbishi et al (2018) in Mansoura University Hospital among children suffered from the various neurological disorders (microcephaly, hydrocephalus, ADHD & epilepsy), collectively grouped as non-syndromic neurological diseases, and Down syndrome, found that IgG seropositivity was significantly higher in non-syndromic neurologically disabled children (63.3%) and Down syndrome (13.3%), when compared to the controls (10%). Although the percentage of seropositive cases in the current study was higher in comparison to the previously mentioned ones, a significant association between presence of anti-Toxoplasma antibodies and neurological diseases could not be established due to the high prevalence of seropositivity also present among controls.…”
Section: Discussionmentioning
confidence: 97%